2006
DOI: 10.1021/jf0611264
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pH on the Kinetics of Acrylamide Formation/Elimination Reactions in Model Systems

Abstract: The effect of pH on acrylamide formation and elimination kinetics was studied in an equimolar (0.1 M) asparagine-glucose model system in phosphate or citrate buffer, heated at temperatures between 120 and 200 degrees C. To describe the experimental data, a simplified kinetic model was proposed and kinetic parameters were estimated by combined nonlinear regression and numerical integration on the data obtained under nonisothermal conditions. The model was subsequently validated in a more realistic potato-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
55
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 29 publications
6
55
0
Order By: Relevance
“…Table 2 summarized the effect of pH on the decrease of ACR mediated by melanoidins. As expected, ACR formation is reduced at low pH and enhanced at higher pH levels (De Vleeschouwer, van der Plancken, van Loey, & Hendrickx, 2006). Increased proton concentration at lower pH will results in a higher amount of protonated amino groups of asparagine.…”
Section: Resultssupporting
confidence: 65%
“…Table 2 summarized the effect of pH on the decrease of ACR mediated by melanoidins. As expected, ACR formation is reduced at low pH and enhanced at higher pH levels (De Vleeschouwer, van der Plancken, van Loey, & Hendrickx, 2006). Increased proton concentration at lower pH will results in a higher amount of protonated amino groups of asparagine.…”
Section: Resultssupporting
confidence: 65%
“…This was due to the increased pH, since no significant difference was assessed with the control mixture at the same pH. In a previous study, it was suggested that phosphate ions exerted an inhibiting effect on acrylamide formation, apart from the pH effect (De Vleeschouwer et al, 2006). This could however not be confirmed in the current model system at the applied concentration level.…”
Section: Influence Of Additives On Acrylamide Formation In Potato Modmentioning
confidence: 54%
“…Comparing the acrylamide contents with the control mixture at the same pH, no significant additional decrease or increase could be detected. The additional acrylamide lowering effect of citric acid, as suggested earlier (De Vleeschouwer et al, 2006), appeared not to be significant and could thus not be confirmed. Similarly, also the other organic acids mitigated acrylamide formation only due to their impact on the product pH, at the applied concentration levels.…”
Section: Influence Of Additives On Acrylamide Formation In Potato Modmentioning
confidence: 70%
See 1 more Smart Citation
“…Glycemic index is lowered when vinegar dressing is added after cooking (Leeman et al 2005). Acrylamide development is reduced in potato products processed at lower pH (Yuan et al 2007;De Vleeschouwer et al 2006) but may be increased if low tissue pH is associated with more reducing sugars.…”
Section: Introductionmentioning
confidence: 99%